Detection of infectious agents and others atherosclerotic factors in patients undergoing cardiac surgery. - Yasser Colao Jiménez; Consuelo Correa Sierra; Vivian Kouri Cardella; Manuel Nafeh Abi-Rezk; Yuliet González Nieves; Mahelys Ramirez Hernández (ECIMED, 2015)
We studied 34 patients, from july 1 to august 31, 2014 at Ameijeiras hospital. A cardiac surgery were performed in all of them, 18 with coronary disease and 16 with valvular disease (10 aortic and 6 mitral) this work was approved by the Ethics Committee responsible for this investigation. We determined they serological status in relation with cytomegalovirus (CMV) and herpes simple virus (HSV) before cardiac surgery and we used samples of tissues during surgery (Left Internal mammary artery, 18.Right Internal mammary artery, 1. Ascending Aortic wall 9, Valvular tissues, 16) to find DNA of cytomegalovirus, herpes simple virus and Clamidophila pneumonia with PCR. The most frecuent risk factor was smoking habit (64,7%), represent 61,1% in coronary disease group and 68,7% in valvulvar. Hypertension was the second one risk factor (58,8%), particulary elevated in coronary disease group(66,6%). The patients in coronary group positive IgG against CMV represent the 77, 7% and with IgG against HSV 66,6%. In the valvular group positive IgG against CMV represent the 68, 7% and with IgG against HSV 56,25%. No one sample of tissue showed genomic presence of C. pneumoniae, CMV or HSV with PCR. Key words: Cardiac Surgery, Atherosclerosis, infection.